การพัฒนาเกณฑ์มาตรฐานการประเมินความเสี่ยงใน การบริหารจัดการทรัพยากรทางกายภาพอาคารสำนักงาน - ทองมา ธงชัย (Academic Journal Phranakhon Rajabhat University, 2017)
This Paper aimed at (1) studying reviewed risk indicator for Facility Management Office Building. With the application of technical research papers, literature synthesis, network data and future research techniques. (2) at developing criteria to assess the risk of Facility Management Office Building and by reviewing of the literature involvement by using the application program (PAJEK) network linking with distance ignorance with main elements and subcomponents of the risk indicators. As for preliminary knowledge about framework in order to strive for the development of risk assessment criteria for Facility Management Office Building, development trends of the risk assessment on the Facility Management Office Building by studying the Ethnographic Delphi Futures Research: EDFR. Round 1 and Round 2 included 17 persons are applied with specialists in Facility Management Office Building. The result of research is composed the 6 aspects 1) Risk for Technology 2) Risk for Quality Control 3) Risk for Management 4) Risk for Handover 5) Risk for Safety 6) Risk for Operation. Among high competition and demand-driven organization with a mission to survive, grow and perform further business with stability and sustainability, all the elements are very important for government and private sector organization which is its advantages of risk management and interest of the management to Facility Management office building for efficiency and effectiveness management.